2020
DOI: 10.1002/trc2.12060
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive medications ameliorate Alzheimer's disease pathology by slowing its propagation

Abstract: Introduction Mounting evidence supports an association between antihypertensive medication use and reduced risk of Alzheimer's disease (AD). Consensus on possible pathological mechanisms remains elusive. Methods Human brain tissue from a cohort followed to autopsy that included 96 cases of AD (46 medicated for hypertension) and 53 pathological controls (33 also medicated) matched for cerebrovascular disease was available from the New South Wales Brain Banks. Quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 38 publications
1
36
1
Order By: Relevance
“…Nonetheless, other interventions may have more subtle effects on amyloid burden, either directly or indirectly. Some examples would be BACE1 inhibitors [ 60 ], drugs with other targets which have downstream amyloid effects [ 61 ], or non-pharmacological therapies and multi-domain preventive trials such as those being tested in World-Wide FINGERS [ 62 , 63 ]. As such, 20% reduction of amyloid accumulation may be a relevant target to detect, especially in a short 1-year Proof-of-Concept study.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other interventions may have more subtle effects on amyloid burden, either directly or indirectly. Some examples would be BACE1 inhibitors [ 60 ], drugs with other targets which have downstream amyloid effects [ 61 ], or non-pharmacological therapies and multi-domain preventive trials such as those being tested in World-Wide FINGERS [ 62 , 63 ]. As such, 20% reduction of amyloid accumulation may be a relevant target to detect, especially in a short 1-year Proof-of-Concept study.…”
Section: Discussionmentioning
confidence: 99%
“…Treating hypertension with medication may at least partially moderate these negative effects on brain health. For example, a recent autopsy study of 96 AD cases and 53 pathological controls found that antihypertensive medication use was associated with a less extensive spread of AD pathology in the brain [ 227 ].…”
Section: Promoting Successful Cognitive Agingmentioning
confidence: 99%
“…25 Eight studies (also) performed logistic regression analysis, with (history of) hypertension, AHM use, or SBP and DBP as continuous predictors, and dichotomized NP and NFT or Braak and CERAD as outcomes. 22,23,27,29,[30][31][32][33] Another four studies (also) performed ordinal regression analysis, predicting categorical measures of NP and NFT with continuous measures of BP, history of hypertension, and/or AHM use. 20,[26][27][28]…”
Section: Statistical Analysis Methods Usedmentioning
confidence: 99%
“…Ten were from the United States, [19][20][21][22][23][24][25][26][27][28] three from Europe, [29][30][31] one from Australia, 32 and one from Asia (Sri Lanka). 33 Ten collected clinical data prospectively before death, 19,20,22,23,[25][26][27][28][29]31 four retrospectively after death, 24,30,32,33 and one before and after death. 21 Ten studies included community-dwelling older people, recruited from the general population and/or retirement homes.…”
Section: Study Design and Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation